Liquefied natural gas as marine bunker : feasibility and future prospect - Lee, Yu Jia (2018)
The purpose of this paper is to conduct a feasibility analysis on the utilization of LNG as bunker fuel as well as its future prospect. In 2005, Annex VI of the International Convention for the Prevention of Pollution from Ships (MARPOL Convention) entered into force to regulate the amount of sulphur oxide emission from ships using fuel with sulphur content. Over the years, there has been a progressive reduction in terms of the emission cap. The current global limit for sulphur content of ships’ bunkers is at 3.50% m/m. With a seismic shift of sulphur fuel cap in 2020 to 0.5% m/m, the search for an alternative cleaner fuel to meet regulatory requirement has gone underway. The methodology used in this research paper is to find out the various drivers and restraining forces (i.e. force field analysis) in using LNG as a marine fuel. By taking a macro view, this paper will focus on 3 main areas, namely the infrastructures supporting LNG, storage and usage of LNG on-board ships, as well as policy framework in place supporting LNG.